Care for patients with cerebrovascular disease in a general hospital. 2 years experience - Joan Omar Rojas Fuentes; Yainelí Cutiño Maas; Ricardo Verdecia Fraga; Ada Sánchez Lozano; Didiesdle Herrera Alonso; Julio López Arguelles (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Background: The care of patients with cerebrovascular disease requires an organized system from pre-hospital care until discharge of the patient, to ensure the continuity of rehabilitation. In order to provide differentiated services to patients with this condition was created in the General Hospital Universitario "Dr. Gustavo Lima Aldereguía "a specialized room for attention to these diseases and the rehabilitation of patients. Objective: To determine the benefits obtained with differentiated services to patients with cerebrovascular disease in a general hospital. Methods: Descriptive case series that included 1038 patients admitted to the specialized chamber for cerebrovascular disease. We analyzed the following variables: stay, type of cerebrovascular disease, clinical classification, the Barthel index and discharge status. Results: 972 patients suffered from cerebrovascular disease, hospital stay was reduced by two days, the attention of specialized equipment increased from 51.75% to 79.2% patients were discharged with a mild degree of functional dependence. Conclusions: The differentiated services to cerebrovascular disease in general hospitals shows benefits for patients.